Hadhanah dalam Islam (Hak Pengasuhan Anak dalam Sektor Pendidikan Rumah) - Achmad Muhajir (SAP (Susunan Artikel Pendidikan), 2017)
Producing qualified learners is inseparable part of education center we know by the term three centers of education; namely home education, school education, and environmental education (community). The three centers of education must be mutually related (support each other) because it is difficult to produce quality learners without paying attention to the three education centers. However, from the three education centers, it is home education creating more astsar (impact) on thedevelopment of learners. In Islamic terms, the activity of educating children is called hadhanah. Hadhanah is love of Allah for His servants by taking care of children who are born from the mother's womb. Parenting is one of manifestation of the various forms of glory Allah has given to humans who are the most glorious beings and is His gift to mankind not given to any other creature. This study istitled "Hadhanah in Religion (Parenting Rights in a home education sector)". The purpose of this study is to find out how a religion gives a concept of parenting so that the children get their full rights, namely getting physical and spiritual education from his parents. The qualitative method used in writing this study explores the concepts of parenting.